O trabalho por trás dos muros altos : um estudo comparativo sobre a qualidade de vida no trabalho dos agentes penitenciários do sistema prisional do estado de Mato Grosso - Massuia, Fernanda Mariano (2019)
Work activities are a privileged space of human achievement, but such activities can also produce (depending on the conditions under which it is exercised) physical and emotional exhaustion. The objective of this study was to understand and compare the perception of Prison Agents of prison units in the interior and capital of the state of Mato Grosso regarding the Quality of Life at Work perspective (QWL) through indicators and factors of QWL, identifying which of these are more significant to this population in order to measure positive or negative outlook (s) in their labor activities. For the development of this exploratory descriptive research, the use of a questionnaire for data collection was used, the results of the questionnaire were cataloged and analyzed using statistical methods via Cronbach's alpha, followed by Pearson's multiple correlations and, finally, by demonstration of results using the comparative matrix method. The analysis of the results pointed out that the Prison Agents (PAs) in the prison units investigated (capital x interior), in their majority, consider their Quality of Life at Work satisfactory. Some of the assumptions observed by the analysis of the data cross-referenced the association of better QWL of the (PAs) given the influence of the public policies of the State of Mato Grosso focused on penitentiary restructuring adopted in the State as of 2011, related to the characteristic factor of work and labor relations, which involved the hiring of new (PAs) and servers of technical areas, training and qualification of servers, career restructuring, creation of the functional portfolio, release of the institutional and state weapons possession (PAs), expansion of the career, acquisition of safety and work equipment, new vehicles, among other actions.